2016
DOI: 10.1002/lsm.22536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photon induced photoacoustic streaming (PIPS) on bond strength to dentine of two root canal filling materials

Abstract: Within the limitations of this study, it was found that the application of the PIPS technique did not have an affect on the push-out bond strength of Resilon/RealSeal SE root canal filling to dentin nor on the gutta-percha/AH Plus. A significant difference in bond strength was noted between the two root canal filling materials. Lasers Surg. Med. 48:951-954, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…RSSE displayed adhesive and mixed failure modes, suggesting that the sealer adheres well to the Resilon core but less predictably to dentin. The mentioned findings are consistent with the results reported in previous studies [ 41 , 49 ]. The adhesive failures suggest an improper chemical bond between the sealer and root canal dentine.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…RSSE displayed adhesive and mixed failure modes, suggesting that the sealer adheres well to the Resilon core but less predictably to dentin. The mentioned findings are consistent with the results reported in previous studies [ 41 , 49 ]. The adhesive failures suggest an improper chemical bond between the sealer and root canal dentine.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, RSSE presented the weakest adhesion force to the dentinal surface (1.059 ± 1.240). These values are in concordance with results reported by other studies [ 29 , 41 , 42 ]. Specifically, in the study released by Stelzer et al [ 29 ], bond strength values ranged between 0.91 ± 0.64 and 1.28 ± 0.60 when hypochlorite, EDTA, or chlorhexidine were used for the final irrigation, with higher levels for hypochlorite followed by saline solution (2.35 ± 0.49).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…66 In the latter, PIPS outperformed LAI (Er:YAG, Nd:YAG, diode lasers), PUI, and EndoVac. Nevertheless, the three other studies did not remark on the improved penetration caused by PIPS versus CSI, 26,70 MAI, 71 and EndoVac (Table 5). 26 Irrigant Penetration in Dentinal Tubules Only one study 69 was found on irrigant penetration into dentinal tubules.…”
Section: Root Canal Sealer Bond Strengthmentioning
confidence: 92%